2022
DOI: 10.3324/haematol.2021.279800
|View full text |Cite
|
Sign up to set email alerts
|

The IL32/BAFF axis supports prosurvival dialogs in the lymphoma ecosystem and is disrupted by NIK inhibition

Abstract: Aggressive B-cell malignancies, such as mantle cell lymphoma (MCL), are microenvironment-dependent tumors and a better understanding of the dialogs occurring in lymphoma protective ecosystems will provide new perspectives to increase treatment efficiency. To identify novel molecular regulations, we performed a transcriptomic analysis based on the comparison of circulating (n=77) versus MCL lymph nodes (n=107) together with RNA sequencing of malignant (n=8) versus normal B-cell (n=6) samples. This integrated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
(98 reference statements)
0
13
0
Order By: Relevance
“…In contrast, whereas stromal cells protected MCL cells against spontaneous apoptosis, they were not able to promote robust proliferation in this model. Based on integrated transcriptomic and functional analysis, they showed that peripheral blood MCL cells cultured in the presence of CD40-L and cytokine stimuli displayed cellular (proliferation, survival) and molecular (NF-kB pathways, Bcl-2 family, secretome) profiles similar to the ones seen in lymph-node-resident MCL cells, emphasizing the relevance of the model and the role of CD40-L expressing T cells for tumor survival [28,33,36]. Further characterization of MCL TME in situ is now needed to characterize these T-cell populations.…”
Section: Cd40-cd40 Ligand Axismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, whereas stromal cells protected MCL cells against spontaneous apoptosis, they were not able to promote robust proliferation in this model. Based on integrated transcriptomic and functional analysis, they showed that peripheral blood MCL cells cultured in the presence of CD40-L and cytokine stimuli displayed cellular (proliferation, survival) and molecular (NF-kB pathways, Bcl-2 family, secretome) profiles similar to the ones seen in lymph-node-resident MCL cells, emphasizing the relevance of the model and the role of CD40-L expressing T cells for tumor survival [28,33,36]. Further characterization of MCL TME in situ is now needed to characterize these T-cell populations.…”
Section: Cd40-cd40 Ligand Axismentioning
confidence: 99%
“…More recently, Decombis et al demonstrated that MCL cells also present a tumorspecific secretion of interleukin-32 beta (IL32β) through CD40-L-mediated interaction with the TME, but also IL32 locus hypomethylation. This secretion is dependent on the alternative NF-κB pathway (NF-kB2) and is able to differentiate monocytes into specific CD163 macrophages, supporting MCL cell survival through a soluble dialog mostly driven by BAFF (a member of the tumor necrosis factor (TNF) family), making the IL32/BAFF axis a novel key target to be disrupted, potentially targeting the NIK/NF-kB2 pathway [36]. The role of the BAFF/BAFF-R axis in the pathogenesis of MCL has also been supported in other studies [42][43][44][45].…”
Section: Monocytes/macrophages and Dynamic Interaction Between MCL Ce...mentioning
confidence: 99%
“…The third group of cells which modulate the survival of lymphoma cells are the macrophages. MCL cells attract monocytes and promote them to differentiate into tumor-associated M2 macrophages (TAM) [ 37 , 38 ]. The precise role for TAMs in MCL is still unknown, although recent studies indicate that TAMs induce MCL growth via secretion of, e.g., IL-10 and BAFF [ 32 , 37 , 38 ].…”
Section: (Dys)regulation Of Bcl-2 Family Proteins In MCLmentioning
confidence: 99%
“…MCL cells attract monocytes and promote them to differentiate into tumor-associated M2 macrophages (TAM) [ 37 , 38 ]. The precise role for TAMs in MCL is still unknown, although recent studies indicate that TAMs induce MCL growth via secretion of, e.g., IL-10 and BAFF [ 32 , 37 , 38 ]. Interestingly, T cells also play a role by CD40-mediated induction of IL-32β, which in turn instructs the TAMS to secrete BAFF [ 38 , 39 ].…”
Section: (Dys)regulation Of Bcl-2 Family Proteins In MCLmentioning
confidence: 99%
See 1 more Smart Citation